1993
DOI: 10.1523/jneurosci.13-05-01932.1993
|View full text |Cite
|
Sign up to set email alerts
|

Expression of AMPA-selective glutamate receptor subunits in morphologically defined neurons of the mammalian cochlear nucleus

Abstract: Glutamate and related amino acids mediate fast excitatory neurotransmission in the vertebrate CNS via ligand-gated cationic channels in the neuronal membrane. These channels are composed of different subunits that assemble into a functional receptor/channel complex. Although studies have shown that these subunits are differentially expressed in neurons, few studies have quantitatively addressed the cell-specific expression of glutamate subunits in relation to known glutamatergic pathways. In the vertebrate aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 59 publications
9
43
0
1
Order By: Relevance
“…However, many brainstem neurons express mostly GluR3 and GluR4, e.g., in the thalamus (Sato et al, 1993b; this study). An example of preferential expression of GluR3 and GluR4 is in the anteroventral cochlear nucleus, where these subunits may be the major subunits in auditory synapses (Hunter et al, 1993;Wang et al, 1997;this study). In support of this, calcium-permeable AMPA receptors, presumably lacking GluR2, have been described in the avian cochlear nucleus (Otis et al, 1995).…”
Section: Glur2-containing Receptors Are Common In the Telencephalon Amentioning
confidence: 65%
“…However, many brainstem neurons express mostly GluR3 and GluR4, e.g., in the thalamus (Sato et al, 1993b; this study). An example of preferential expression of GluR3 and GluR4 is in the anteroventral cochlear nucleus, where these subunits may be the major subunits in auditory synapses (Hunter et al, 1993;Wang et al, 1997;this study). In support of this, calcium-permeable AMPA receptors, presumably lacking GluR2, have been described in the avian cochlear nucleus (Otis et al, 1995).…”
Section: Glur2-containing Receptors Are Common In the Telencephalon Amentioning
confidence: 65%
“…Although the present study did not map fractional concentrations in sensory areas projecting to these thalamic relays, there are reasons to expect that these also have AMPA receptors of the AR-2,3 type (i.e., enriched in GluR -3 and -4 relative to GluR1). In the auditory system, the spiral ganglion (Ryan et al, 1991;Safieddine and Eybalin, 1992;Niedzielski and Wenthold, 1995), cochlear nuclei (Hunter et al, 1993), and other auditory brainstem nuclei (Sato et al, 1993) are enriched in the GluR2, GluR3, and/or GluR4 subunits. The retina also has GluR2, GluR3, and GluR4 mRNA levels that are high relative to concentrations of GluR1 mRNA (Hamassaki-Britto et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The particular subunits that compose this "fast" receptor are unknown. However, studies using in situ hybridization to identify the mRNA of various AMPA-receptor subunits in the cochlear nucleus of rats indicated that neurons innervated by the auditory nerve expressed GluR2, GIuR3, and GluR4, but not GluRl (Hunter et al, 1993;Sato et al, 1993). It will be interesting to determine whether this pattern of expression has any bearing on the rapidity of the response of AMPA receptors to glutamate.…”
Section: Channel Conductances and Open Timesmentioning
confidence: 98%